Model Pelayanan Pemuda Remaja Berdasarkan Prinsip Pembinaan 1 Timotius 4:8-12 dalam Meningkatkan Partisipasi Ibadah - Rahellea Andera (Sekolah Tinggi Teologi Berita Hidup, 2026)
This study aims to describe the conditions of youth participation in the Pentecostal Church Region III North Bengkulu, describe the responsibility of the church as a faith community to prepare youth as successors of church service in the future, describe the principles of development in the book of 1 Timothy 4: 8-12, describe a service model that is in accordance with the principles of development in 1 Timothy 4: 8-12 and in accordance with the needs of youth in service in the Pentecostal Church Region III North Bengkulu. This study uses a method with a descriptive qualitative research approach..Data collection techniques were carried out through observation, interviews, and documentation. The interviews in this study used the interview format.Focus Group Discussion(FGD). The participants involved in this study were the Pastor, youth mentor, youth ministry administrator and youth of the Pentecostal Church Region III North Bengkulu. The results of the study show the five Principles of Formation in the book of 1 Timothy 4: 8-12, giving priority to spiritual training, conveying reliable teachings, providing service motivation, encouraging to preach and teach the truth of the word and emulating the life of the leader. The condition of youth participation in the Pentecostal Church Region III North Bengkulu, there are variations in the existence of special youth services in churches, with some churches having special youth services, while others do not, the number of youth who attend varies, with some churches having youth who rarely attend in significant numbers. Churches that have special youth services tend to have a higher number of youth who attend compared to those that do not have special services. An effective ministry model for youth includes a variety of activities such as progressive spiritual formation, mentoring, small communities, digital ministry, participatory ministry, and creative activities that enable the church to reach young people holistically, spiritually, socially, and emotionally. Penelitian ini bertujuan untuk mendeskripsikan kondisi partisipasi pemuda remaja di Gereja Pentakosta Wilayah III Bengkulu Utara, mendeskripsikan tanggung jawab gereja sebagai komunitas iman untuk mempersiapkan pemuda remaja sebagai penerus pelayanan gereja di masa depan, mendeskripsikan prinsip-prinsip pembinaan dalam kitab 1 Timotius 4 : 8 – 12, mendeskripsikan model pelayanan yang sesuai dengan prinsip pembinaan 1 Timotius 4 : 8 - 12 serta sesuai dengan kebutuhan pemuda remaja didalam pelayanan di Gereja Pentakosta Wilayah III Bengkulu Utara. Penelitian ini menggunakan metode dengan jenis pendekatan penelitian kualitatif deskriptif. Teknik pengumpulan data dilakukan melalui observasi, wawancara, dan dokumentasi. Wawancara dalam penelitian ini menggunakan bentuk wawancara Focus Group Discussion (FGD). Adapun partisipan yang terlibat dalam penelitian ini yaitu Gembala sidang, pembina pemuda remaja, pengurus pelayanan pemuda remaja dan pemuda remaja Gereja Pentakosta Wilayah III Bengkulu Utara. Hasil penelitian menunjukkan lima Prinsip Pembinaan dalam kitab 1 Timotius 4 : 8 – 12, memberikan prioritas latihan rohani, menyampaikan ajaran yang dapat dipercaya, memberikan motivasi pelayanan, mendorong untuk memberitakan dan mengajarkan kebenaran firman serta meneladani hidup dari pemimpin. Kondisi partisipasi pemuda remaja di Gereja Pentakosta Wilayah III Bengkulu Utara, terdapat variasi dalam keberadaan ibadah khusus pemuda di gereja-gereja, dengan beberapa gereja memiliki ibadah khusus pemuda, sementara yang lain tidak, jumlah pemuda yang rajin datang bervariasi, dengan beberapa gereja memiliki pemuda yang jarang datang dalam jumlah yang signifikan. Gereja yang memiliki ibadah khusus pemuda cenderung memiliki jumlah pemuda yang lebih rajin datang dibandingkan dengan yang tidak memiliki ibadah khusus. Model pelayanan yang efektif untuk kaum muda mencakup berbagai kegiatan seperti pembentukan spiritual progresif, pendampingan, komunitas kecil, pelayanan digital, pelayanan partisipatif, dan kegiatan kreatif yang memungkinkan gereja untuk menjangkau kaum muda secara holistik, spiritual, sosial, dan emosional.